Strindberg on drama and theatre a source book - Strindberg, August 1849-1912 (Amsterdam University Press, 2007)
Painter, photographer, alchemist - but ultimately, playwright, and outstanding playwright at that - the figure of August Strindberg (1849-1912) towers over late-nineteenth century drama. Strindberg's electrifying theatrical work resonated with the public in his own lifetime, and continues to impress audiences around the globe today. A restless innovator of various dramatic forms, he served as a source of inspiration for legendary figures like Eugene O' Neill, Samuel Beckett, and Ingmar Bergman, and proved seminal to the development of modern drama as we know it. Though Strindberg's preface to Miss Julie and his prefatory note to A Dream Play are well known, Strindberg's frequent commentary on drama and theatre in general are less familiar, as are most of his plays. Strindberg on Drama and Theatre presents the most important of these comments, chronologically assembled and annotated, many of them published for the first time in English. An essential resource for those interested in one of our most modern playwrights, as well as a thrilling read for the dedicated theatre lover, Strindberg on Drama and Theatre provides a fascinating look at one of our most powerful dramatic voices